Psychological Aspects of the Main Character in the Movie “If I Stay” - Rengganis Wijayanti, Dewa Ayu; Sudipa, I Nengah; Weddha Savitri, Putu (Humanis, 2018)
The paper entitled Psychological Aspect of the Main Character in The Movie “If I Stay” aims to describe the psychological aspect of the main character and how this aspect affects the main character’s behavior or personality. The topic is interesting because this movie has some tragedies that happen and affect the main character’s life in terms of view of psychological aspect which made this movie have an agitation to be analyzed. The data of this study were taken from a movie entitled If I Stayby using the documentation method. The collected data were analyzed by using a qualitative method based on the theoretical framework. The data were categorized based on the Psychological theory proposed by Bernhardt (1953). The r esults of the interpretation of the data reveale that the main character has all the psychological aspects in her life and  some of them mostly affect her behavior and personality.